How Do Political Actors on Social Media Drive Public Interest and Participation? - Khori Aulia Ria Anggraeni; Roni Jayawinangun; Ahsani Taqwim Aminuddin (International Journal of Business, Economics, and Social Development, 2026)
The intensification of political actors communication on social media has reshaped patterns of public political engagement, yet the mechanisms linking these interactions remain contested. This study examines the influence of political actors’ communication on political interest and political participation among residents of Bogor, while also evaluating whether political interest mediates this relationship. Using linear regression and a mediation analysis with PROCESS Model 4, the results show that political actors’ communication significantly increases political interest (B = 0.559; p < 0.05) and political participation (B = 0.316; p < 0.05). However, political interest does not significantly affect participation (B = 0.033; p > 0.05) and does not serve as a mediator, as indicated by a non-significant indirect effect (LLCI = –0.0064; ULCI = 0.0439). These findings reveal a direct-only effect, suggesting that political participation is driven more by impression-based and emotionally framed digital communication than by cognitive processes rooted in political interest. Beyond its statistical conclusions, this study underscores how social media environments can prompt individuals to engage in political behaviors even in the absence of strong intrinsic interest, highlighting the performative, immediate, and affective nature of political communication in digital spaces. Overall, the study enriches the understanding of contemporary political engagement by demonstrating that affective cues and online visibility play a more dominant role than traditional interest-based motivations, aligning with the principles of Communication Mediation Theory and Impression Management in the context of modern political communication.